An Analysis of Lexical Coherence in Fereydoun Tavallali’s Al-Tafasil from the perspective of functional Linguistics - Gholamreza Salimi; Zahra Rafie; Alireza Biaban Navard Sarvestani (مطالعات زبانی و بلاغی)
Fereydoun Tavallali was among the most significant contemporary artists who established a new genre in Persian satirical writing. Due to such innovations, he maintained a decisive and influential presence in the literary and political circles in Iran for almost a quarter of a century. Despite the passage of time and the obsolescence of the sociopolitical events of that era, Tavallali's satire has maintained its charm for the Persian speaking audience. Seemingly, a crucial reason for the fineness of his satire is his command of text-based and functional linguistics. Regarding functional linguistics, text coherence is considered as a crucial component of literary works. Michael Halliday's theory of lexical coherence and Ruqaiya Hasan's theory of cohesion and cohesive harmony are among the most practical contemporary theories through which one can acknowledge the degree of coherence and magnetism of a work such as Al-Tafasil by Tavallali. This research uses a descriptive-analytical approach to investigate Tavallali's satires, with an emphasis on Halliday and Hassan's theory of lexical coherence. The results show that Tavallali has utilized the elements of lexical cohesion to create the satire in Al-Tafasil in a way that such elements have enhanced the coherence of structure and content of his satire and given more depth to his intended concepts. He has employed word repetition to enhance the coherence of the overall context in a novel way and has also used Saj' (rhymed prose) to create coherence and cohesion among successive sentences. Tavallali’s use of paronomasia, morphological derivations and alliteration has also merged the successive sentences in a solid sequence. Regarding the harmony of words, he has also made an innovative use of congeries, contrasts and synonyms; the use of contrasts is very proportionate and synonyms are used less often. Instead of using -congeries in one sentence, they are used separately in short sentences, which brings about the higher frequency of verbs and conjunctions in the text. Tavallali has thus deepened the internal coherence of the text with an enhancement of musicality and tone and has aligned the language with his political, critical and revolutionary goals.